Caffeine effects on short-term performance during prolonged exercise in the heat - Del Coso, J.; Estevez, E.; Mora-Rodriguez, R. (Medicine & Science in Sports & Exercise, 2008)
Purpose: To determine the effect of water, carbohydrate, and caffeine ingestion on fatigue during prolonged exercise in the heat.